No role for direct touch using the pectoral fins, as an information gathering strategy in a blind fish. - Windsor, S; Paris, J; de Perera, T (2011)
Blind Mexican cave fish (Astyanax fasciatus) lack a functional visual system and have been shown to sense their environment using a technique called hydrodynamic imaging, whereby nearby objects are detected by sensing distortions in the flow field of water around the body using the mechanosensory lateral line. This species has also been noted to touch obstacles, mainly with the pectoral fins, apparently using this tactile information alongside hydrodynamic imaging to sense their surroundings. This study aimed to determine the relative contributions of hydrodynamic and tactile information during wall following behaviour in blind Mexican cave fish. A wall was custom built with a 'netted' region in its centre, which provided very similar tactile information to a solid tank wall, but was undetectable using hydrodynamic imaging. The fish swam significantly closer to and collided more frequently with the netted region of this wall than the solid regions, indicating that the fish did not perceive the netted region as a solid obstacle despite being able to feel it as such with their pectoral fins. We conclude that the touching of objects with the pectoral fins may be an artefact of the intrinsic link between pectoral fin extensions and tail beating whilst swimming, and does not function to gather information. During wall following, hydrodynamic information appears to be used strongly in preference to tactile information in this non-visual system.